Developing new Pyrido[2,3-d]pyrimidine -Based Small-Molecule as potent ATR Inhibitors - Ghous, Faraz; kirubakaran, sivapriya (Synlett)
Ataxia Telangiectasia and Rad3-related (ATR), a key enzyme of the phosphatidylinositol 3-kinase-related kinase (PIKK) family, that plays a vital role in controlling the DNA damage response (DDR). ATR has become more essential for the survival of tumour cells that have deficiencies in the ataxia telangiectasia mutated (ATM) gene or a lack of DDR function. This indicates that ATR is an important target for anticancer drugs due to its synthetic lethality. In this article, we present a potent and highly selective pyrido[2,3-d]pyrimidine based novel ATR inhibitor. All the synthesized compounds were characterized by using 1H NMR, 13C NMR, and HRMS analysis, and they were all produced in good to excellent yields. In-silico studies were conducted on a synthesized compound (4a) using density functional theory (DFT) at B3LYP/6-311++G(d,p) level. Results showed good predictions for pharmacokinetics, medicinal properties, physicochemical, and lipophilicity. ADMET studies predicted target molecule properties and simulated molecular docking between ligand and receptors.